The key physical parameters governing frictional dissipation in a precipitating atmosphere - Makarieva, A.M.; Gorshkov, V.G; Nefiodov, A.V; Sheil, D.; Nobre, A.D; Bunyard, P; Li, B.L. (American Meteorological Society, 2013)
Precipitation generates small-scale turbulent air flows—the energy of which ultimately dissipates to heat. The power of this process has previously been estimated to be around 2–4 W m−2 in the tropics: a value comparable in magnitude to the dynamic power of global atmospheric circulation. Here it is suggested that the true value is approximately half the value of this previous estimate. The result reflects a revised evaluation of the mean precipitation pathlength HP. The dependence of HP on surface temperature, relative humidity, temperature lapse rate, and degree of condensation in the ascending air were investigated. These analyses indicate that the degree of condensation, defined as the relative change of the saturated water vapor mixing ratio in the region of condensation, is a major factor determining HP. From this theory the authors develop an estimate indicating that the mean large-scale rate of frictional dissipation associated with total precipitation in the tropics lies between 1 and 2 W m−2 and show empirical evidence in support of this estimate. Under terrestrial conditions frictional dissipation is found to constitute a minor fraction of the dynamic power of condensation-induced atmospheric circulation, which is estimated to be at least 2.5 times larger. However, because HP increases with increasing surface temperature Ts, the rate of frictional dissipation would exceed the power of condensation-induced dynamics, and thus block major circulation, at Ts ≳ 320 K in a moist adiabatic atmosphere.